Conversations about time - Lucas, Gavin 1965-; Olivier, Laurent 1958- (Routledge, 2022)
"This book presents a conversation between two prominent archaeologists who have been exploring the concept of time in their discipline for several decades. It is a discussion on key issues of time in archaeology filtered through their unique perspectives, which sometimes meet and at other times, clash. Key features include discussions on the nature of change and time in the archaeological record, the relation between the present and past, the connection between time and the goals of archaeology and the relevance of the Anthropocene to disciplinary practice. Situated in how the authors own views on the topic of time have developed over their careers, the conversation offers an intimate and personal insight into how two leading scholars think and debate a topic of central importance to the discipline. All archaeologists with an interest in contemporary theory and the topic of time will find this book of relevance, but also the student who wants to a front row seat onto a live debate on this topic will find it an invaluable complement to the more traditional textbook"--
"Routledge Focus"--from cover
Keywords: Archäologie; Zeitlichkeit; Archaeology / Methodology; Time / Philosophy; Archaeology / Philosophy; Lucas, Gavin / 1965- / Interviews; Olivier, Laurent / 1958- / Interviews; Interviews